2008
DOI: 10.1111/j.1934-6093.2006.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Studies On Human Body Sway By Using A Simple Model With Special Concerns On The Pelvic And Muscle Roles

Abstract: The human pelvis is such a unique structure that enables our upper body to work so perfectly with the two legs so as to control the body's balance in the complicated postures. The aim of this study is to establish a new dynamic body sway control model in the upright standing body position in coronal plane, and to reveal the possible control mechanisms underlying the body sway with special concerns on the roles that the pelvis and its muscles are performing during the sway. The plant of control model, the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…As the idiopathic scoliotic patients are otherwise healthy, identifying these patients before the onset of scoliosis in order to obtain their patterns of sagittal profile is difficult [7]. Hence we turn to simulations to test the hypothesis that there is an association between the sagittal curvature and deformity patterns of the spine [3,14,17]. A reduced order model of the pediatric spine for studying scoliosis was proposed by Pasha [21].…”
Section: Introductionmentioning
confidence: 99%
“…As the idiopathic scoliotic patients are otherwise healthy, identifying these patients before the onset of scoliosis in order to obtain their patterns of sagittal profile is difficult [7]. Hence we turn to simulations to test the hypothesis that there is an association between the sagittal curvature and deformity patterns of the spine [3,14,17]. A reduced order model of the pediatric spine for studying scoliosis was proposed by Pasha [21].…”
Section: Introductionmentioning
confidence: 99%
“…For normal balance ability, the postural control mechanism can be illustrated using different postural models. The single-link model is a simple approach to simulate the postural control mechanism in the anterior-posterior (AP) direction at the ankle joint [9,10]. Angular velocity and acceleration are the primary factors that maintain the body s stability [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of postural control mechanism in the medio-lateral (ML) direction, a different method can be used to acquire the model. The relationship of contractions of two muscles, such as the gluteus medius and psoas major muscles, is an example of postural models in the ML direction and was derived by Jiang et al [9]. Although these models were acquired by different methods, the outcomes from the models such as torque of joint are the primary variables to re ect the balance control mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For minimizing psychological influence, subjects were asked to numerate on mind while doing standing task. A study from eight healthy young subjects [13] shown that the body sways scope of ankle and lumbosacral were 0.94±0.36degree (eye-open), 1.35±0.52degree (eye-closed) and 0.99±0.41degree (eye-open), 1.27±0.72degree (eye-closed), respectively. No significant difference existed between the ankle and lumbosacral.…”
Section: Upright Standing and Body Swaymentioning
confidence: 99%
“…Using a force sheet to measure COP deviation, we recorded the surface EMG activities of m. tibialis anterior (TA), m. peroneus longus (PL) and Caput mediale m. gastrocnemii (MG) when asked subjects standing on one foot. The relationship between COP deviation and muscular activities was identified [13] (Fig.5).…”
Section: The Roles Of Foot In Balance Controlmentioning
confidence: 99%